A Study of the Effects of Cognitive Mapping on Reading Comprehension and Written Protocols. Technical Report No. 7 - Ruddell, Robert; Boyle, Owen; Learning from Text Project, Riverside, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
A study explored how cognitive mapping assists college students in gathering information from long prose passages and organizing this information for subsequent writing. Mapping is a prewriting technique in which students develop a cognitive scheme or graphic representation of a text, which reduces memory load and facilitates integration and retention of information. It was hypothesized that mapping would help improve students' writing fluency and cohesion, as well as assist them in identifying main ideas and supporting details in articles. The 51 undergraduate subjects were tested prior to and after introduction to and practice with mapping techniques, to assess their ability to analyze and synthesize the six passages in the Organizational Patterns Test (OPT) and to write about them. The OPT contains three different organizational patterns: informational, thesis-proof, and problem-solution. In the pretest, students in all three treatment groups were given 10 minutes to prepare to write their essays. In the posttest, students in two of the treatment groups were given 10 minutes to map the OPT articles before writing essays, while those in the third treatment group prepared for the essays using an organizational preparation of their choice. The results indicated the subjects in the two mapping groups scored higher on the essays, used a greater number of cohesive ties, and wrote longer essays than did the nonmapping subjects. There was no difference between groups in ability to identify main ideas and supporting details. (HTH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Mapping; Cognitive Processes; Cohesion (Written Composition); Higher Education; Language Processing; Reading Comprehension; Reading Processes; Reading Research; Retention (Psychology); Study Skills; Writing (Composition); Writing Improvement; Reader Text Relationship -- Text Structure; Reports, Research